Screening of constituents of the essential oil of Satureja montana in the potential treatment of COVID 19 using computational methods - Vasilić, Đorđe; Erić, Slavica (Archives of Pharmacy, 2022)
Constituents of essential oil of Satureja Montana (SM) were investigated in aim of elucidation of potential activities on viruses that can be transcribed in genetic material, such are SARS CoV 2 and HIV. Chemical structures of constituents (34) of the SM essential oil were built and geometry optimized using ChemDraw ultra 8.0 and Chem3D Pro 8.0 programs. Prediction of potential interactions for each constituents with large number of targets was performed by SwissTargetPrediction program. Results indicate that constituents, with certain level of probability, can be involved in interactions with some targets significant for antiviral activity, in direct or indirect mode, such are adenosine receptors type 1, UDP-glukuronosyltransferases, receptor-dependent transport channels, peroxisome-proliferator activated receptor alpha, GLI 2, as well as some other targets. Since in this work just constituents of SM essential oil were investigated, further studies should be directed towards investigation of full content of SM, in various solvents, for elucidation of mechanisms of action of this plant in therapy of viremias, presumably for supposed inhibition of transcription of viruses.